Problems associated with indoor air quality (IAQ) in classroom and recommended approaches - Suhaimi, M. A.; A. Rahman, M. A.; Awang, Mariah; Akasah, Z. A.; Hashim, N. (Pusat Penyelidikan dan Inovasi Politeknik, Jabatan Pendidikan Politeknik, 2017)
School has become a major center of education and development of children in many countries around the world. During the school day, majority of the students spend most of their time in school in the classroom. Therefore, it is very important for the school to ensure that every classroom has good indoor air quality. Imbalance IAQ can contribute to Sick Building Syndrome (SBS) as well as Building-Related Illness (BRI) and thereby affect the health and productivity of students in the classroom. This situation certainly does not reflect the national education goals which aim to produce a good and perfect human capital with good features through a series of effective education. Therefore, this study aims to discuss problems related to IAQ and measures that can enhance the quality of indoor environment of a classroom at school. As a result, the study found that the most common problems associated with IAQ adversely affect the health of students and their performance. Meanwhile, a good quality of indoor environment in the classroom can be achieved through an emphasis on good design, construction and renovation of buildings as well as continuous maintenance practices. In conclusion, a good classroom environment will have a beneficial effect on health and thus can increase the productivity of students.